2011
DOI: 10.4081/reumatismo.2007.66
|View full text |Cite
|
Sign up to set email alerts
|

Synoviocyte cultures from synovial fluid

Abstract: The study of the pathogenetic mechanisms of rheumatic diseases is in general carried out through “in vitro” systems based on cellular cultures models. The difficulties to achieve fresh human tissue prompted us to develop a simpler method to obtain fibroblast-like synovial cells from synovial fluid (SF). Methods: SF was collected from the knees of 5 patients with rheumatoid arthritis (RA), 4 with osteoarthritis (OA) and 5 with psoriatic arthritis (PsA). The pellet obtained after centrifugation was resuspended i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…Synovial cells (containing macrophage-like and fibroblast-like synoviocytes) were isolated from tissue explants and cultured as previously described [10]. Briefly, tissues were minced and incubated with a solution containing 0.15 mg/ml DNase, 0.15 mg/ml hyaluronidase (type I-S), and 1 mg/ml collagenase (type IA) (Sigma-Aldrich) in Dulbecco’s modified Eagle’s medium (DMEM; Invitrogen, Carlsbad, CA, USA) for 1 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Synovial cells (containing macrophage-like and fibroblast-like synoviocytes) were isolated from tissue explants and cultured as previously described [10]. Briefly, tissues were minced and incubated with a solution containing 0.15 mg/ml DNase, 0.15 mg/ml hyaluronidase (type I-S), and 1 mg/ml collagenase (type IA) (Sigma-Aldrich) in Dulbecco’s modified Eagle’s medium (DMEM; Invitrogen, Carlsbad, CA, USA) for 1 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…It is possible that the high production of antioxidants enzymes are due to the Nrf2 activation by ROS, like in the TPH-1 cells activation exposed to MSU with the intention of compensating the cellular stress state [34]. In the particular case of gout and other microcrystalline arthropathies, it is known that crystals increase the production of NO − [35], and if it combines with O 2 − , peroxynitrite (ONOO − ) is produced, affecting cellular proliferation, degradation of connective tissue structures, and degeneration of joint tissue [36][37][38].…”
Section: Oxidative Stress Mechanisms In Goutmentioning
confidence: 99%
“…Lines inside the boxes represent the median. Statistical signiWcance was set at P · 0.05 Studies have demonstrated that FLS obtained from synovial Xuid (SF) showed the phenotype and the reactivity of synovial tissue FLS [28,33]. Neidhart et al [53] demonstrated that similar to tissue-derived RA FLS, FLS from RA synovial Xuid, which contain "Xoating" anchorage-independent Wbroblast-like cells, mediate cartilage destruction independent of the hyperplastic synovial tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Adherent cells were fed with the same media every 3-5 days and passaged every 7-14 days. The methods were described previously by Scanu et al [28]. Normal synovial tissues were obtained from 13 patients undergoing joint surgery after injury.…”
Section: Laboratory Examination Of Immunological Parametersmentioning
confidence: 99%
See 1 more Smart Citation